Lack of an association between the functional polymorphism TREM-1 rs2234237 and the clinical course of sepsis among critically Ill caucasian patients—a monocentric prospective genetic association study - Runzheimer, Julius; Schmack, Bastian (Journal of Clinical Medicine, 2019)
Sepsis is a life-threatening condition and a significant challenge for those working in intensive care, where it remains one of the leading causes of mortality. According to the sepsis-3 definition, sepsis is characterized by dysregulation of the host response to infection. The TREM-1 gene codes for the triggering receptor expressed on myeloid cells 1, which is part of the pro-inflammatory response of the immune system. This study aimed to determine whether the functional TREM-1 rs2234237 single nucleotide polymorphism was associated with mortality in a cohort of 649 Caucasian patients with sepsis. The 90-day mortality rate was the primary outcome, and disease severity and microbiological findings were analyzed as secondary endpoints. TREM-1 rs2234237 TT homozygous patients were compared to A-allele carriers for this purpose. Kaplan–Meier survival analysis revealed no association between the clinically relevant TREM-1 rs2234237 single nucleotide polymorphism and the 90-day or 28-day survival rate in this group of septic patients. In addition, the performed analyses of disease severity and the microbiological findings did not show significant differences between the TREM-1 rs2234237 genotypes. The TREM-1 rs2234237 genotype was not significantly associated with sepsis mortality and sepsis disease severity. Therefore, it was not a valuable prognostic marker for the survival of septic patients in the studied cohort.